2022
DOI: 10.1111/aos.15254
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic window of opportunity in the acute uveitic phase of Vogt–Koyanagi–Harada disease: Prevention of late autoimmune complications by early intervention

Abstract: Purpose To determine relationship between timing of treatment initiation and disease outcomes and whether a therapeutic window of opportunity exists in initial‐onset acute uveitis associated with Vogt–Koyanagi–Harada disease. Methods Retrospective analysis of 112 patients (224 eyes). Main outcome measures were final visual acuity, progression to chronic recurrent evolution, development of complications, particularly ‘sunset glow fundus’, and drug‐free remission cure of uveitis. Results Forty‐six patients (92 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous studies also demonstrated that subretinal pooling of fluorescein over the posterior pole was more frequently observed in patients who presented early within 2 weeks of symptoms compared to those presenting after 2 weeks (Chee et al., 2010; Yang et al., 2007). These findings suggest that the absence of peripapillary punctate choroidal hyperfluorescence, punctate choroidal hyperfluorescence elsewhere and patches of hypofluorescence that corresponded to areas of exudative retinal detachment on pretreatment ICGA are poor prognostic factors as it suggests that the choroidal inflammation is no longer within the therapeutic window of opportunity (Abu El‐Asrar et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies also demonstrated that subretinal pooling of fluorescein over the posterior pole was more frequently observed in patients who presented early within 2 weeks of symptoms compared to those presenting after 2 weeks (Chee et al., 2010; Yang et al., 2007). These findings suggest that the absence of peripapillary punctate choroidal hyperfluorescence, punctate choroidal hyperfluorescence elsewhere and patches of hypofluorescence that corresponded to areas of exudative retinal detachment on pretreatment ICGA are poor prognostic factors as it suggests that the choroidal inflammation is no longer within the therapeutic window of opportunity (Abu El‐Asrar et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of VKH disease in the acute uveitic phase was based on the pattern of clinical characteristics at presentation. Patients with initial‐onset uveitis associated with VKH disease typically showed bilateral exudative retinal detachment and optic nerve head hyperaemia and swelling with (delayed presentation) or without (early presentation) AS inflammation (Abouammoh et al., 2016; Abu El‐Asrar, Al Mudhaiyan, et al., 2017; Abu El‐Asrar et al., 2012, 2023; Abu El‐Asrar, Dosari, et al., 2017) (Figure 1). We only included the patients who had ICGA performed before initiating treatment with a minimum follow‐up of 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations